Analisis Kualitas Produk Boomerang Table untuk Mengurangi Cacat Produksi Menggunakan Metode Six Sigma di PT XYZ - Aldi Armananta; Noor Nailie Azzat (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2026)
PT XYZ is a furniture manufacturing company producing Boomerang Table products. However, its production process continues to experience a relatively high defect rate, resulting in increased production costs, rework activities, and reduced customer satisfaction. Based on the 2024 production data, the defect rate reached 3.14%, with a Defects Per Million Opportunities (DPMO) value of 10,458 and a sigma level of 3.82σ. This study aims to identify the dominant types of defects, evaluate the production process capability, analyze the root causes of defects, and propose improvement strategies using the Six Sigma methodology through the DMAIC (Define, Measure, Analyze, Improve, and Control) framework. This research employed a descriptive quantitative approach with a case study design based on PT XYZ's production data collected throughout 2024. The results indicate that the dominant defects were non-conforming dimensions (38.1%), scratched surfaces (23.1%), and uneven color (14.1%). Fishbone analysis identified six major factors contributing to product defects, namely human, machine, material, method, measurement, and environmental factors. Based on these findings, several improvement initiatives were proposed, including operator training, machine calibration and preventive maintenance, standard operating procedure (SOP) revision, implementation of in-process inspection, enhancement of material quality control, and improvement of the production environment. The proposed improvements are projected to reduce the DPMO to 3,200, increase the sigma level to 4.25σ, and improve the process yield to 99.68%. The findings demonstrate that the implementation of the Six Sigma methodology is effective in improving production quality and can serve as a practical reference for continuous quality improvement in the furniture manufacturing industry.